2014
DOI: 10.1016/j.bbamcr.2014.03.005
|View full text |Cite
|
Sign up to set email alerts
|

The TMEFF2 tumor suppressor modulates integrin expression, RhoA activation and migration of prostate cancer cells

Abstract: Cell adhesion and migration play important roles in physiological and pathological states, including embryonic development and cancer invasion and metastasis. The type I transmembrane protein with epidermal growth factor and two follistatin motifs 2 (TMEFF2) is expressed mainly in brain and prostate and its expression is deregulated in prostate cancer. We have previously shown that TMEFF2 can function as a tumor suppressor by inhibiting cell migration and invasion of prostate cells. However, the molecular mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 47 publications
(72 reference statements)
3
14
0
Order By: Relevance
“…Inducing TMEFF2 expression after tumor formation did not significantly impede growth or result in tumor regression (not shown), suggesting that TMEFF2 may be functioning in the early stages of the allograft establishment/progression. These results are consistent with a tumor suppressor role for TMEFF2 that we have previously reported .…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Inducing TMEFF2 expression after tumor formation did not significantly impede growth or result in tumor regression (not shown), suggesting that TMEFF2 may be functioning in the early stages of the allograft establishment/progression. These results are consistent with a tumor suppressor role for TMEFF2 that we have previously reported .…”
Section: Resultssupporting
confidence: 93%
“…Based on these results we speculated that TMEFF2, by affecting one carbon metabolism, may epigenetically affect gene expression. In fact, we have observed decreased αv, β1 and β3 integrin expression in PCa and benign cell lines overexpressing TMEFF2 and in the double TMEFF2/TRAMP transgenic mouse when compared with the TRAMP mouse . Therefore, the role of TMEFF2 in prostate regeneration could be facilitated by its effect on integrin expression via its role in metabolism.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…based on a number of studies, upregulated RhoA is associated with tumor progression in different types of cancer (33)(34)(35) and RhoA activation promotes the migration of cervical, colon and hepatocellular carcinoma (36)(37)(38). However, significantly downregulated expression of RhoA was demonstrated in human conventional RCC compared to that in normal kidney tissues (17) and activated RhoA has specifically been shown to inhibit the migration of breast and prostate cancer (39,40). Here, we indicated that activation of RhoA/ROCK/MLC signaling by honokiol suppresses the migration of RCC (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This interaction results in decreased levels of sarcosine (Chen et al, 2011a; Green et al, 2013), an amino acid associated with PCa progression (Sreekumar et al, 2009). Full length TMEFF2 also attenuates the migratory properties of PCa cells (Chen et al, 2014), indicating a tumour suppressor function. However, the TMEFF2‐ECD released, due to shedding, may act as a soluble growth factor.…”
Section: Introductionmentioning
confidence: 99%